1996
DOI: 10.1046/j.1365-2141.1996.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary acute leukaemias with 11q23 rearrangement: clinical, cytogenetic, FISH and FICTION studies

Abstract: Three patients with secondary acute leukaemia after treatment with topoisomerase II inhibitor agents are described. Two patients had acute myeloid leukaemia (AML). FAB M5a, one had pro-B-acute lymphoblastic leukaemia (ALL). The interval between initiation of chemotherapy and the onset of secondary acute leukaemia was 19-20 months. 11q23 rearrangements were detected in all cases. They were due to translocations t(11;19) (q23;p13.3), t(11;16)(q23;p13) and t(4;11)(q21;q23), respectively. Fluorescence in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Showing that treatment may exclude topoisomerase II inhibitors [12][13][14] or may include only an intercalating topo II inhibitor combined with alkylating agents with radiation 15 or alone. 16 The present study suggests that secondary hematological malignancies with 11q23 abnormalities may arise following a wider variety of treatment regimens than initially supposed. In particular, prior treatment with anthracyclines appeared to be at least as important as the use of epipodophyllotoxins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Showing that treatment may exclude topoisomerase II inhibitors [12][13][14] or may include only an intercalating topo II inhibitor combined with alkylating agents with radiation 15 or alone. 16 The present study suggests that secondary hematological malignancies with 11q23 abnormalities may arise following a wider variety of treatment regimens than initially supposed. In particular, prior treatment with anthracyclines appeared to be at least as important as the use of epipodophyllotoxins.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, patients treated with topo II inhibitors have been shown to have the shortest latent periods of 2-3 years, 8,16 compared with 5-10 years following treatment with alkylating agents and 6-8 years following radiation treatment. 2,8 Among the Workshop patients, one of the shortest latent periods (10 months) followed treatment with an alkylating agent and antimetabolite for myeloma while the longest latent period (8 years) for patients for whom treatment was known followed treatment of ovarian carcinoma with epipodophyllotoxin, anthracycline, alkylating agents and other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…5 The present finding of treatment-related leukemias in approximately 5% of the cases was also expected, although only a few studies have focused on therapy-associated ALL with 11q23/MLL rearrangements, as opposed to the well-known association between secondary AML and exposure to DNA topoisomerase II inhibitors. 56,57 A review of the literature, however, reveals that all published therapy-associated t(4;11)-positive ALL, in which treatment was specified, had received chemotherapy targeting DNA topoisomerase II, ie etoposide, teniposide, doxorubicin, epidoxorubicin and mitoxantrone. 5 A detailed discussion on therapy-related 11q23 malignancies collected by the Workshop, including the present 10 cases, is found in Secker-Walker et al 58 The majority of the 183 cases of leukemia displayed t(4;11) as the sole change; additional, or secondary, changes were seen in only 30% of the cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results indicated that the MLL gene, on chromosome band 11q23, is one of the two partner genes in the t-AML with t(11;16). [17][18][19] The MLL gene (for mixed lineage leukemia), also known as ALL-1, HRX, or Htrx-1, has been shown to participate in many recurring rearrangements (reviewed in Ref. 20).…”
Section: Introductionmentioning
confidence: 99%